Entre os saberes e os dizeres africanos na Educação Profissional e Tecnológica-EPT: um estudo sobre as religiões de matrizes africanas e a intolerância religiosa no IFAP, campus Macapá e Santana - ROLLA, Marlene Barreto (2025)
This research will analyze African-based religions and religious intolerance in the school environment, carried out at IFAP, Macapá and Santana campuses, with the general objective of analyzing the conceptions that students and teachers have in relation to African-based religions and the possible acts of religious intolerance experienced by their followers in the school environment. The specific objectives are: to identify elements of Afro-Brazilian culture and its religiosity in the statements of students and educators, as well as to identify their main conceptions and prior knowledge on the subject, analyzing their stereotypes and whether they have already witnessed cases of religious intolerance at the Institute. To this end, we used qualitative research as a research method, with semi-structured interviews, the data of which were analyzed through Thematic Analysis. In the theoretical framework, we based ourselves on authors such as Paulo Freire, Nilma Gomes and Stella Caputo, among others. And, as an educational product, we created an educational website with the aim of assisting the learning of the institution's students and, in this way, we hope that with the results of this research we can contribute to the development of more inclusive pedagogical strategies of appreciation and respect for religious diversity within IFAP. Keywords: Afro-Brazilian religions; religious intolerance; diversity and respect.